2020
DOI: 10.1021/acsami.9b19986
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing Latex: A Route to Complex Geometries of High Molecular Weight Polymers

Abstract: Vat photopolymerization (VP) additive manufacturing fabricates intricate geometries with excellent resolution; however, high molecular weight polymers are not amenable to VP due to concomitant high solution and melt viscosities. Thus, a challenging paradox arises between printability and mechanical performance. This report describes concurrent photopolymer and VP system design to navigate this paradox with the unprecedented use of polymeric colloids (latexes) that effectively decouple the dependency of viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 32 publications
0
62
0
Order By: Relevance
“…[40,41] However, the implementation of highmolecular-weight polymers in photocuring process such as SLA remains challenging. Some recent attempts focused on SLA of nonreactive styrene-butadiene rubber latex [42] dispersed in poly(ethylene glycol) dimethacrylate resin leading after photopolymerization to a continuous biphasic system. Here, the formulation of SEBS-g-VCHO and ELO appears to be a more stable resin formulation than latex formulation over time and therefore probably more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…[40,41] However, the implementation of highmolecular-weight polymers in photocuring process such as SLA remains challenging. Some recent attempts focused on SLA of nonreactive styrene-butadiene rubber latex [42] dispersed in poly(ethylene glycol) dimethacrylate resin leading after photopolymerization to a continuous biphasic system. Here, the formulation of SEBS-g-VCHO and ELO appears to be a more stable resin formulation than latex formulation over time and therefore probably more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…196 Recent work by Scott et al showed that the formation of a physically entangled high molecular weight polymer network between layers could also be used to improve the interlayer adhesion strength. 198 Additives that promote the homogenization of the polymer network have also been shown to be effective in increasing the interlayer adhesion strength. 199 Green and Guymon demonstrated that the incorporation of a small amount of cyanomethyl dodecyl trithiocarbonate, a RAFT agent, into a photoresin enabled the reinitiation of polymer chains at the surface during the curing process and increased the number of covalent attachments that could be made between layers.…”
Section: Materials Chemistry To Improve Interlayer Adhesion In Vpmentioning
confidence: 99%
“…[30] Importantly, in such systems, high molecular weight polymers can be used without increase in dispersion viscosity. [31] Despite the fact that the thixotropy of latex dispersions has been known for a long time and even used in inkjet printing, [32] nanocolloidal hydrogel inks formed solely from attractive percolating latex NPs have not been reported for 3D printing of functional materials.…”
Section: Introductionmentioning
confidence: 99%